2016
DOI: 10.1080/19768354.2016.1267041
|View full text |Cite
|
Sign up to set email alerts
|

Cell specific stress responses of cadmium-induced cytotoxicity

Abstract: Cadmium is one of the age old toxic heavy metal, detrimental to the biological system. In this study, we explored the cellular and molecular mechanisms induced on exposure to different concentrations of cadmium chloride (CdCl 2 ), on three different human cell lines with wild type p53, viz., A549, HEK293 and HCT116. We investigated whether the cellular responses followed, displayed any specific pattern related to their viability, mitochondrial respiration, DNA damage and apoptotic gene expression. All the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In fact, previous studies demonstrated that Cd exhibits dosedependent toxicity on different cell lines. 30 However, these preliminary in vitro results should be complemented with further experiments to further evaluate the observed cell-type specificity.…”
Section: Cytotoxicity Of the Coordination Polymersmentioning
confidence: 99%
“…In fact, previous studies demonstrated that Cd exhibits dosedependent toxicity on different cell lines. 30 However, these preliminary in vitro results should be complemented with further experiments to further evaluate the observed cell-type specificity.…”
Section: Cytotoxicity Of the Coordination Polymersmentioning
confidence: 99%
“…Thus, prostate cancer cells with insufficient p53 expression or those expressing mutant p53 are resistant to Cd-induced apoptosis 29 . In contrast, a protective role of p53 against Cd-induced cytotoxicity has been reported in A549, HEK293, and HCT116 cells 30 . In that study, Cd exposure downregulated p53 at the transcriptional level in wild-type HCT116 (p53 +/+ ) cells.…”
Section: Discussionmentioning
confidence: 88%
“…In the development of this assay, all test compounds were solubilised in DMSO, although the solubility of cadmium chloride in DMSO (1800 g/l (25 °C) is similar to in water [1400 g/l (25 °C)], it is possible that the acoustic dosing technologies utilised in this assay may not be compatible with dosing metal salt solutions. In multiple cell lines, Cadmium induced DNA damage is observed at relatively high doses that are associated with cytotoxicity (500, 1000 and 2000 µM) 44 furthermore A549 cells have been shown to exhibit tolerance towards cadmium induced cell death when compared to other lines (HEK293, HC116p53wt and HC116p53 −/− and CHO-9) 45 , 46 , highlighting the potential cell line and dose specific effects of this compound that may contribute to the lack of response observed in this assay. To assess this prolonged treatment regimens, with and without the inclusion of a recovery period, as well as a broader dose range could be assessed.…”
Section: Discussionmentioning
confidence: 99%